System transformation for growth and sustainability : ocean energy in Portugal - Fontes, Margarida (2019)
ABSTRACT: This Report presents the results of research conducted for the OECD Project on Systems Transformation, undertaken in the framework of the Working Party on Innovation and Technology Policy (TIP). It conveys the results of the Portuguese Case Study. The OECD project on Systems Transformation (2015-2016) corresponded to the second phase of the System Innovation Project (https://www.innovationpolicyplatform.org/systeminnovation-oecd-project) whose objective was to help policy makers re-think innovation policies in the context of sustainability and green growth. It built on and extended the previous work, by applying the policy lessons learned to concrete cases of transitions in the field of knowledge based industrial production and in the area of sustainability. The goal of the project was to study advanced practices in policy support for the promotion of emerging industries and sustainable (green) innovations in OECD economies, focusing on the role of selected policy tools, such as cluster policies, demonstrators, technology roadmapping, and smart regulation. The project aimed at identifying good practices for designing these innovation policy instruments, based on a series of comparative case studies. The Portuguese Case Study addressed the role of systemic policies in the construction of an Ocean Energy System, i.e. a system that originates from the development and diffusion of renewable energies based on the ocean, providing an opportunity to examine how sustainability and structural change goals can be combined.